Analisis Faktor Yang Mempengaruhi Kualitas Hidup Pada Lansia dengan Diabetes Melitus Tipe 2 di Kota Malang - Yahya, Wilma Shintari; Wardojo, Sri Sunaringsih Ika; Yuliadarwati, Nungki Marlian (NHM PRESS, 2023)
Diabetes mellitus is a complex metabolic disorder characterized by hyperglycemia, which is an abnormal condition characterized by increased blood glucose levels caused by partial or total insulin insufficiency. Caused by two main factors, namely the occurrence of damaged insulin secretion in pancreatic β cells and the inability of the tissue to insulin to respond to insulin properly. Patients with type 2 diabetes mellitus have a low quality of life. This study used a cross-sectional study method. The research was conducted at the Pandanwangi Health Center in Malang City and the Dinoyo Health Center in Malang City from late March to early April 2023. The sample size for this study was 35 respondents. The research instruments were DQOL-BCI and MMAS-8. The analysis used to test the hypothesis in this study is multiple linear test analysis. the results of multiple linear analysis tests obtained a significant value for the duration of suffering from DM of 0.025 with a value of B being a minus value, which means that the longer you suffer from DM, the quality of life in the elderly with type 2 DM decreases. The conclusion from this study is that there are factors that influence quality of life in the elderly with type 2 diabetes mellitus in Malang City, namely the long-suffering factor.